Lingkungan Belajar di Era Digital: Telaah Hadis Tarbawi dan Relevansinya dengan Pembelajaran Modern dalam Tinjauan Studi Maudhui - Muhammad Ihsan Mubarok; Romlah Abubakar Askar; Miftahuddin; Aji Sentosa (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The development of digital technology has brought about major changes in the education system, particularly in the interaction patterns and learning environments of students. On the one hand, technology provides easy access to information and learning flexibility, but on the other hand, it also poses challenges in the form of decreased social interaction, weak learning etiquette, and reduced spiritual values ​​in the educational process. This study aims to examine the concept of the learning environment from the perspective of the tarbawi hadith and its relevance to modern learning in the digital era. The study used a qualitative approach with a library research method. Primary data were obtained from hadiths in Kutub As-Sittah related to the assembly of knowledge, learning etiquette, and the blessings of the educational environment, while secondary data came from books, journals, and relevant literature. Data analysis was carried out using the tahqiq al-hadith approach, fiqh al-hadith, and thematic analysis (maudhu'i). The results of the study indicate that the learning environment according to the tarbawi hadith includes three main aspects, namely the physical, social, and spiritual environment. The physical environment is related to the provision of learning facilities and technology that support the learning process. The social environment is manifested through respect for teachers, positive interactions, and collaborative learning in the science assemblies. Meanwhile, the spiritual environment is reflected through the practice of prayer, dhikr, and maintaining blessings in the learning process. These three aspects are relevant to modern learning principles such as student-centered learning, collaborative learning, and flexible learning. Therefore, integrating the values ​​of the Tarbawi hadith into digital learning is crucial to creating a learning environment that focuses not only on technological and academic mastery but also on the development of character, etiquette, and spirituality in students.